Neuroprotective effect of Myo/Nog cells in the stressed retina. (May 2016) - Bravo-Nuevo, Arturo; Brandli, Alice A.; Gerhart, Jacquelyn; Nichols, Jennifer; Pitts, Meghan; Sutera, Christopher K.; Assali, Sarah; Scheinfeld, Victoria; Prendergast, George C.; Stone, Jonathan; George-Weinstein, Mindy
Abstract: Myo/Nog cells are essential for eye development in the chick embryo and respond to injury in adult tissues. These cells express mRNA for the skeletal muscle specific transcription factor MyoD, the bone morphogenetic protein (BMP) inhibitor Noggin and the cell surface protein recognized by the G8 monoclonal antibody (mAb). In this study, we determined that Myo/Nog cells are present in low numbers in the retina of the mouse eye. G8-positive Myo/Nog cells were distinguished from neuronal, Müller and microglial cells that were identified with antibodies to calretinin, Chx10, glial fibrillary acidic protein and ionized calcium binding adaptor molecule 1, respectively. In the neonatal retina, the number of Myo/Nog cells increased in parallel with cell death induced by transient exposure to hyperoxia. In this model of retinopathy of prematurity, depletion of Myo/Nog cells by intravitreal injection of the G8 mAb and complement increased cell death. These findings demonstrate that Myo/Nog cells are a distinct population of cells, not previously described in the retina, which increases in response to retinal damage and mitigate hypoxia-induced cell death.